2022
DOI: 10.3762/bjnano.13.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drug concentration and PLGA addition on the properties of electrospun ampicillin trihydrate-loaded PLA nanofibers

Abstract: The aim of this study was to produce ampicillin trihydrate-loaded poly(lactic acid) (PLA) and PLA/poly(lactic-co-glycolic acid) (PLA/PLGA) polymeric nanofibers via electrospinning using 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) as the solvent for local application in tissue engineering. The effects of ampicillin trihydrate concentration (4–12%) and addition of PLGA (20–80%) on the spinnability of the solutions, morphology, average nanofiber diameter, encapsulation efficiency, drug release, and mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Throughout the 12 h experiment, the dissolution profiles showed sustained release, with no case exceeding 20% of the total Doxy amount released. The sustained drug release from PLA-based nanofibers is consistent with findings reported in the literature [ 53 , 54 ]. Previous research has proven the possibility of using this type of fiber for the prolonged release of drugs or biomolecules [ 55 , 56 ].…”
Section: Resultssupporting
confidence: 90%
“…Throughout the 12 h experiment, the dissolution profiles showed sustained release, with no case exceeding 20% of the total Doxy amount released. The sustained drug release from PLA-based nanofibers is consistent with findings reported in the literature [ 53 , 54 ]. Previous research has proven the possibility of using this type of fiber for the prolonged release of drugs or biomolecules [ 55 , 56 ].…”
Section: Resultssupporting
confidence: 90%
“…It was observed that the incorporation of 3HF(B) led to a decrease in the average nanofiber diameter, typically ranging from 114±20 nm for pristine nanofibers to about 80±40 nm for drug‐loaded nanofiber. This could be attributed to the interaction between the polymer and drug molecule through hydrogen bonding which in turn increased the crystallinity of the nanofiber mat [28,29] …”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to the interaction between the polymer and drug molecule through hydrogen bonding which in turn increased the crystallinity of the nanofiber mat. [28,29]…”
Section: Field Emission Scanning Electron Microscopy (Fesem) Analysismentioning
confidence: 99%
“…Conversely, as the concentration of both shellac and extract increased, a significant reduction in the efficiency of entrapment was detected. The potential cause of this decrease could be the existence of immobile constituents in the solution or the substances’ poor solubility [ 70 ]. These findings provide valuable insights into the interplay between solution composition and entrapment efficiency, offering guidance for optimizing electrospinning conditions to achieve effective incorporation of components within the fibers for various applications in materials science.…”
Section: Discussionmentioning
confidence: 99%